High-Speed Architectures for Parallel Long BCH Encoders. - Zhang, X. (IEEE Transactions on VLSI systems)
Long Bose?Chaudhuri?Hocquenghen (BCH) codes are used as the outer error correcting codes in the second-generation Digital Video Broadcasting Standard from the European Telecommunications Standard Institute. These codes can achieve around 0.6-dB additional coding gain over Reed?Solomon codes with similar code rate and codeword length in long-haul optical communication systems. BCH encoders are conventionally implemented by a linear feedback shift register architecture. High-speed applications of BCH codes require parallel implementation of the encoders. In addition, long BCH encoders suffer from the effect of large fanout. In this paper, three novel architectures are proposed to reduce the achievable minimum clock period for long BCH encoders after the fanout bottleneck has been eliminated. For an (8191, 7684) BCH code, compared to the original 32-parallel BCH encoder architecture without fanout bottleneck, the proposed architectures can achieve a speedup of over 100%.